The Effect of the Project-Based Learning Model on the 4C Skills (Critical Thinking, Creativity, Communication, and Collaboration) of Elementary School Students - Amroni, Yolanda Syafitri; Hidayah, Nurul; Firmansah, Deri; Fiah, Rida El (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This research aims to examine the effect of the project-based learning model on elementary school students' 4C skills. This research is a quasi-quantitative experimental research. The sampling technique used at the SD Negeri 2 Perm Way Kandis location was an arbitrary cluster technique. The research sample consisted of two groups: experimental class IV A, totaling 28 students, and control class IV B, totaling 30 students. Data collection techniques use tests and questionnaires. Data analysis techniques use normality tests, homogeneity tests, and hypothesis tests. The results of data analysis can be used to identify the impact of critical thinking skills and creativity. The average pretest score for the experimental class was 40.89, the posttest score was 81.07, the average pretest score for students in the control class was 44, and the posttest score was 80.16, higher in the experimental class than the control class. Based on the analysis of experimental class student questionnaire data, the questionnaire data was used as a measuring tool for students' level of skill achievement, communication, and collaboration in the experimental and control classes, and an average score of 82 was obtained. Furthermore, the average score for the control class was 79.5. The results of the t-test using the SPSS StatisticsV for Windows application obtained a value of Sig<0.05(5) on Sig(two-sided), namely 0.000<0.05(5) for 28 students. Based on this research, PJBL has a significant impact on improving students' 4C skills.